Motivated motive selection in the lying-dictator game - Kai Barron; Robert Stüber; Roel van Veldhuizen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
A large body of evidence suggests that people are willing to sacrifice personal material gain in order to adhere to a moral motive such as fairness or truth-telling. Yet less is known about what happens when moral motives are in conflict. We hypothesize that in such situations, individuals engage in what we term `motivated motive selection', choosing to adhere to the motive that most closely aligns with their personal interest. We test this hypothesis using a laboratory experiment that induces in subjects a conflict between two of the most-studied moral motives: fairness and truth-telling. Our experimental design has the attractive features of being both parsimonious and closely related to both the classic dictator and lying games, implying comparability with a wealth of benchmark evidence. In line with our hypothesis, our results suggest that participants are more likely to adhere to the motive that is more in line with their self-interest.
Keywords: C91; D01; D63; D90; 330; Motivated reasoning; dictator game; lying game; motives; moral dilemma